2018
DOI: 10.1021/acs.macromol.8b02144
|View full text |Cite
|
Sign up to set email alerts
|

Phase Separation and Self-Assembly in Vitrimers: Hierarchical Morphology of Molten and Semicrystalline Polyethylene/Dioxaborolane Maleimide Systems

Abstract: Vitrimers -a class of polymer networks which are covalently crosslinked and insoluble like thermosets, but flow when heated like thermoplastics -contain dynamic links and/or crosslinks that undergo an associative exchange reaction. These dynamic crosslinks enable vitrimers to have interesting mechanical/rheological behavior, self-healing, adhesive, and shape memory properties.We demonstrate that vitrimers can self-assemble into complex meso-and nanostructures when crosslinks and backbone monomers strongly inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
225
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(238 citation statements)
references
References 89 publications
12
225
1
Order By: Relevance
“…The molecular weight and dispersity of this commercial polymer (i 8 = 11 kg/mol and Đ = 7.5) were reported previously. 56 Figure 3A features the horizontal shift factors (@ A ) determined by shifting the PE SAOS tan E data ( Figure S4C) However, the ∆J &2( determined from creep is 16 ± 1 kJ/mol, matching the value of the virgin polymer ( Figure S14D). These findings are consistent with the observations of van Gurp and Palmen.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…The molecular weight and dispersity of this commercial polymer (i 8 = 11 kg/mol and Đ = 7.5) were reported previously. 56 Figure 3A features the horizontal shift factors (@ A ) determined by shifting the PE SAOS tan E data ( Figure S4C) However, the ∆J &2( determined from creep is 16 ± 1 kJ/mol, matching the value of the virgin polymer ( Figure S14D). These findings are consistent with the observations of van Gurp and Palmen.…”
Section: Resultsmentioning
confidence: 84%
“…Ricarte, Tournilhac, and Leibler showed that polyethylene/dioxaborolane vitrimers self-assemble into nanostructures. 56 Chen, Li, and Torkelson further observed microphase separation in molten polybutadiene and polydimethylsiloxane vitrimers with hydroxyurethane cross-links. 57 In this work, we show that self-assembly and phase separation have a significant impact on the rheology and, consequently, processability of vitrimers.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…[14] Recently,N icolaþ, Leibler, and co-workers disclosed fascinating covalent exchangeable vitrimers crosslinked by dynamic exchange of boronate ester linkages,a lthough the actual exchange mechanism still remains unsolved. [24][25][26] To the best of our knowledge,n one of the dynamically crosslinked materials described so far reach the very high glass transition temperatures (T g above 200 8 8C) required for adhesives,p rotective coatings,l ow-wear,o rl ow-friction materials when exposed to high temperatures (contact with hot parts,c omposites for aerospace,e lectronics,b earings). Fors uch demanding applications,o nly af ew thermoplastics constituted of very rigid segments,w ith various degrees of solubility and processability are commercially available (for example,p olyaryletherketones,p olyethersulfones,p olyaramides,p olyetherimides,o rp olybenzimidazoles).…”
Section: Introductionmentioning
confidence: 99%